Direct interaction of DNA repair protein tyrosyl DNA phosphodiesterase 1 and the DNA ligase III catalytic domain is regulated by phosphorylation of its flexible N-terminus - Rashid, Ishtiaque (J Biol Chem, 2021)
Tyrosyl DNA phosphodiesterase 1 (TDP1) and DNA Ligase IIIα (LigIIIα) are key enzymes in single-strand break (SSB) repair. TDP1 removes 3′-tyrosine residues remaining after degradation of DNA topoisomerase (TOP) 1 cleavage complexes trapped by either DNA lesions or TOP1 inhibitors. It is not known how TDP1 is linked to subsequent processing and LigIIIα-catalyzed joining of the SSB. Here we define a direct interaction between the TDP1 catalytic domain and the LigIII DNA-binding domain (DBD) regulated by conformational changes in the unstructured TDP1 N-terminal region induced by phosphorylation and/or alterations in amino acid sequence. Full-length and N-terminally truncated TDP1 are more effective at correcting SSB repair defects in TDP1 null cells compared with full-length TDP1 with amino acid substitutions of an N-terminal serine residue phosphorylated in response to DNA damage. TDP1 forms a stable complex with LigIII(170–755), as well as full-length LigIIIα alone or in complex with the DNA repair scaffold protein XRCC1. Small-angle X-ray scattering and negative stain electron microscopy combined with mapping of the interacting regions identified a TDP1/LigIIIα compact dimer of heterodimers in which the two LigIII catalytic cores are positioned in the center, whereas the two TDP1 molecules are located at the edges of the core complex flanked by highly flexible regions that can interact with other repair proteins and SSBs. As TDP1and LigIIIα together repair adducts caused by TOP1 cancer chemotherapy inhibitors, the defined interaction architecture and regulation of this enzyme complex provide insights into a key repair pathway in nonmalignant and cancer cells.